Effects of a sports nutrition bar on endurance running performance - Oliver, S. K.; Tremblay, M. S. (The Journal of Strength and Conditioning Research, 2002)
The Access bar claims to contain adenosine antagonists and a precise mixture of macronutrients that are purported to improve aerobic performance by increasing fat metabolism and providing sustained exogenous energy. The purpose of this research was to examine the effect of the Access bar on endurance running performance. Twelve active, healthy runners completed 5 sessions: a O2max test, a 30-minute familiarization session, and 3 experimental sessions. During each experimental session subjects ran a self-paced, simulated race on a treadmill (approximately 55 minutes) until they had completed a set energy expenditure target (0.8368 kJ × 60 minutes × body mass). Fifteen minutes before exercise subjects received either the Access bar and water, Uncle Tobys Peanut Butter Muesli Bar and water, or Crystal Light, using a randomized, double-blind design. Heart rate, oxygen consumption, respiratory exchange ratio, and running speed were measured every minute during testing. Blood lactate and rating of perceived exertion were assessed at selected intervals; time to finish was also recorded. Analysis of variance showed no significant difference between the 3 treatments in any of the measures. These results do not support the use of the Access Sports Nutrition Bar to enhance endurance running performance of approximately one hour.